Connecting Action Research in English Language Teaching: A Postulation - Khatri, Dipendra Kumar (Journal of NELTA Karnali, 2022)
The paper entitled 'Connecting Action Research in English Language Teaching: A Postulation' aims to explore the theoretical aspects of action research by linking the idea with a particular context where the English language is being taught as a foreign language. It was written by collecting related documents from the library and online sources specifically. The resources were sorted out to make them relevant to the selected issue. Specifically, the books and generally, some articles were reviewed mainly for the literature and made a list thematically. Then, they were analyzed, interpreted, and connected to the topic. It was concluded that the area of action research is broad and many action kinds of research are being done cyclically in social science. As it is a buzz word in the field of education, particularly in English as a foreign language teaching, the practitioners are requested to connect the action research for the purpose of improving the teaching-learning as well as professional development in this nonnative English situation.